Rapid mobile inspection equipment for metro tunnels based on multi-sensor integration - Fan, Tingli; Mao, Qingzhou; Tang, Chao; Wang, Li; Li, Jiulin; Bao, Yan; Gao, Tao; Pei, Lejun; Zhang, Dongliang; Wang, Yong (Scientific reports, 2025)
The acquisition of tunnel inspection data is fundamental to tunnel operation and maintenance. Existing inspection equipment is either based on laser scanning or CCD cameras. Laser scanning-based devices often struggle to detect cracks, while equipment based on CCD cameras is unable to acquire point cloud to assess tunnel deformations. In order to obtain high-quality, comprehensive data, this paper develops a mobile three-dimensional inspection device CKY-200, integrated with multiple sensors. The CKY-200 addresses the temporal and spatial synchronization issues of CCD cameras and laser scanners. Considering the convenience of inspection, the device progresses on the track powered by electricity. Moreover. This article proposes a tunnel deformation detection algorithm and a crack width measurement method, and verifies the accuracy of the data collected by the equipment. Through on-site experiments and comparison, the CKY-200 provides the advantages of more comprehensive data acquisition while ensuring high precision and speed.